Isolation, Screening and Molecular Cloning Studies of Xylanase Producing Bacillus Pumilus Strains - Hamzah, Ainon (1997)
Cellulosic plant materials are an excellent source of hemicellulolytic microorganisms. Five strains of Bacillus pumilus PJ19, P2, K52A, K51 and K5B, two strains of B. subtilis B2 and PJ18 and one Cellulomonas sp. which produced endoxylanase (1,4-B-D-xylan xylanohydrolase, EC 3.2.1.8) have been isolated locally from plant materials. B. pumilus PJ19 produced the highest xylanase activity when grown in shake flask in yeast tryptone broth (YIB) at 200 rpm, 37°C which yielded activity of 265 U/ml. The enzyme was induced in Dubois media by the addition of xylan as carbon source and was repressed by xylose, glucose, fructose, maltose and sucrose. B. pumilus strain PJ19 and K5B showed maximum enzyme activity when grown in YIB (PH 7.2), 37°C after 36 hours, P2 (28 hours), while K51 and K52A after 32 hours incubation. The xylanase from B. pumilus PJ19 was purified to homogeneity by ammonium sulphate precipitation and gel filtration of CM-Sepharose and Sephacryl S-200. The molecular weight of the purified xylanase was estimated to be 23,000 D by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and 22,SIS D by mass spectrometry. The isoelectric point of the enzyme was 9.3. The optimum pH and temperature for hydrolysis of oat spelt xylan were 6.5 and 60°C, respectively. The enzyme was stable at a pH range of 7.5 to 8.5 and at a temperature of up to 45˚C but lost 50% of its activity at 58°C after 10 minutes of incubation. The purified enzyme had a Km of 1.42 mg/ml and V max of 107 µmol/ minlmg for oat spelt xylan and Km of 2.15 mg/ml and V max of 29.22 µmol/min/mg for birchwood xylan. The major end products of oat spelt xylan hydrolysis were xylobiose, xylotriose and higher oligosaccharides while for birchwood xylan were xylotriose with some xylobiose determined by thin layer chromatography and high performance liquid chromatography. Xylose was not produced as a product of hydrolysis and trans xylosidation was detected. The activity of the enzyme was enhanced in the presence of Mg2+, Ca2+ and K+ but was inhibited by EDTA, Cu2+, Ag+, Zn2+, Fe2+ and Hg2+. The enzyme was competitively inhibited in the presence of xylose with Kj of 1 98 mM. A complete DNA sequence of the xylanase gene was amplified by polymerase chain reaction and cloned into E. coli INVaF' using pCRII cloning vector. The complete DNA sequence was also determined. The structural xylanase gene which started from an ATG initiation codon, consists of an open reading frame of 684 bp, which encoded 202 amino acid residues. The molecular weight of the xylanase was estimated from the amino acid composition to be 22,474 D and is in agreement with the results obtained from SDS-PAGE of the purified xylanase. The xylanase was expressed constitutively by the cloned gene in the absence of xylan. The enzyme was located primarily in the cytoplasm probably because of the incompatibility of the Gram-positive signal peptide in E. coli to direct the enzyme extracellularly as in the donor strain.